Changes in growth, hormones levels and essential oil content of Ammi visnaga plants treated with some bioregulators - IMAN M. TALAAT; HEMMAT I. KHATTAB; AISHA M. AHMED (Nusantara Bioscience, 2013)
Abstract. Talaat IM, Khattab HI, Ahmed AM. 2013. Changes in growth, hormones levels and essential oil content of Ammi visnaga plants treated with some bioregulators. Nusantara Bioscience 5: 57-64. The effects of foliar application of different concentrations of amino acids (tyrosine and phenylalanine) and phenolic acids (trans-cinnamic acid, benzoic acid, and salicylic acid) on growth, pigment content, hormones levels and essential oil content of Ammi visnaga L were carried out during two successive seasons. It is clear that foliar application of either amino acids or phenolics significantly promoted the growth parameters in terms of shoot height, fresh and dry biomass, number of branches and number of umbels per plant. The increment of growth parameter was associated with elevated levels of growth promoters (IAA, GA3, total cytokinins) and low level of ABA. The greatest increase in the previously mentioned parameters was measured in plants exposed to different concentrations of phenols particularly in benzoic acid-treated plants. Such effect was concentration dependent. All treatments led to significant increments in seed yield and essential oil content. Moreover, Gas-Liquid Chromatographic analysis revealed that the main identified components of essential oil were 2,2-dimethyl butanoic acid, isobutyl isobutyrate, ?-isophorone, thymol, fenchyl acetate, and linalool. Phenolics and amino acids treatments resulted in qualitative differences in these components of oil.